Reformulating The Governance Of Regional Owned Enterprise For Drinking Water Services: Improving Legal Procetion In Water Services - Hutapea, Ridho Ribbon; Arya Wijaya, Muhammad; Achmad Darojdat, Tubagus (Journal Evidence Of Law, 2024)
This research aims to analyze the governance of Regional-Owned Enterprises (BUMD) engaged in drinking water services. The focus of this research is the reformulation of BUMD governance to be in accordance with the principles of Good Corporate Governance (GCG) to ensure legal protection for the community. The method used in this research is a normative juridical approach, with reference to various relevant laws and regional regulations. The urgency of this research lies in the urgent need to improve BUMD governance, particularly in the aspects of transparency, accountability, and community participation, given the importance of access to proper drinking water as a basic human right. In addition, this study identifies a research gap in the form of a lack of in-depth studies on the implementation of GCG principles in the context of public services and legal protection in drinking water BUMDs, which has not been widely discussed in previous studies. The results show that the implementation of GCG in BUMD is still not optimal, especially in terms of financial management transparency and internal control. Governance reformulation is needed to improve the effectiveness of BUMDs in providing services that are in line with public standards, as well as strengthening legal protection mechanisms for consumers. This research contributes to providing practical recommendations for local governments to improve BUMD governance, as well as enriching the literature on local enterprise management that focuses on public services and consumer protection.